Term Neonate Presenting with the Combined Occurrence of Mucolipidosis Type II and Leigh Syndrome - Speer, Rebecca R.; Ezeanya, Uzoamaka C.; Beaudoin, Sarah J.; Glass, Kristen M.; Oji-Mmuo, Christiana N. (Journal of Pediatric Genetics, 2020)
Mucolipidosis II α/beta (MLII) is an autosomal recessive disease in which a gene mutation leads to improper targeting of lysosomal enzymes with an end result of accumulation of lysosomes in the mitochondria resulting in a dysfunctional mitochondria.1 Leigh syndrome (LS) is a rare progressive neurodegenerative disorder associated with dysfunctional mitochondria and oxidative phosphorylation.4 Both disease processes typically present in infancy.37 Herein, we present a case of an infant diagnosed with both mucolipidosis II and Leigh syndrome. Genetic analysis in this case revealed two mutations (NDUFA12 c.178C > T p.Arg60* and GNPTAB c.732_733delAA) on the long arm of chromosome 12 as the etiology of MLII and LS in this neonate, respectively. We are unaware of any previously published cases of the presence of these two diseases occurring in the same patient. The complex clinical presentation of this case led to a delay in the diagnosis, and we believe that the clinical phenotypes of these two conditions were likely worsened. The genetic alterations presented in this case occurred as a result of mutations on chromosome 12. We suggest further investigation into the potential overlap in the pathophysiology, specifically the inheritance pattern, linkage disequilibrium, mitochondrial–lysosomal interaction, or crosstalk contributing to both diseases.
Keywords: mucolipidosis II; I cell disease; Leigh syndrome